Principles of environmental medicine: an educational case study of lead poisoning in Beethoven - Thomas C. Erren; Florian Glenewinkel; Andreas Pinger; Philip Lewis (Frontiers in Public Health)
BackgroundUnderstanding the nature and consequences of widespread lead poisoning is critical to protecting people from harm.Educational case studyWe review the historical example of hypothesized lead poisoning in the famous composer Beethoven as an educational vector to illustrate principles of environmental medicine. We discuss what would happen if a hypothetical present-day Mr. B with comparable health complaints, clinical symptoms, or test results were to visit a doctor today. Human biomonitoring – with population reference values and health-based guidance values – is discussed as an important diagnostic tool.ConclusionThis practical outlook on lead poisoning for readers with non-environmental medicine backgrounds contributes to an understanding of principles of environmental medicine.